Modulatory Effects of Alpha- and Gamma-Tocopherol on the Mitochondrial Respiratory Capacity and Membrane Potential in an In Vitro Model of Alzheimer’s Disease - Pahrudin Arrozi, Aslina; Wan Ngah, Wan Zurinah; Ahmad Damanhuri, Hanafi; Makpol, Suzana (Frontiers in Pharmacology, 2021)
Increased amyloid-beta (Aβ) and amyloid precursor protein (APP) in the brains of Alzheimer’s disease (AD) patients are common pathological hallmarks mediating the disease progression. Growing evidence also suggests that mitochondrial abnormalities are an early feature in the pathogenesis of AD. Intervention with antioxidants has received great interest as a molecular strategy for the manipulation of mitochondrial function. Our previous preliminary study using in vitro cell models expressing different types of APP demonstrated that treatment with alpha-tocopherol (ATF) or gamma-tocopherol (GTF) modulates mitochondrial function by reducing mitochondrial reactive oxygen species (ROS), increasing the production of ATP and preventing apoptosis events, especially in cells expressing the mutant APP form. Thus, we hypothesized that ATF or GTF treatment might also alter mitochondrial metabolic pathways such as oxidative phosphorylation. The present study aimed to investigate the role of ATF and GTF in modulating mitochondrial oxidative metabolism using high-resolution respirometry. Our results showed that both ATF and GTF increased the respiratory capacity and membrane potential in the ROUTINE and OXPHOSCI-LINKED states as well as complex IV enzyme activity in wild-type and mutant APP-overexpressing SH-SY5Y cells. Although preliminary, these findings indicate that ATF and GTF modulate mitochondrial oxidative metabolism in APP-overexpressing cells and, in part, may contribute to the planning of strategies for utilizing vitamin E isomers against mitochondrial-related diseases such as AD.